Pelatihan Mindfulness pada Kebahagiaan Penderita Diabetes Melitus Tipe II - Retno Widhianingrum; Subandi Subandi; Rumiani Rumiani (Faculty of Psychology, Universitas Semarang, 2018)
This research aims at identifying the effect of mindfulness training on the happiness fo patients of diabetes melitus type II. The subject of the reseach was 8 patients who will be divided into experimental group and control group. The data collection was conducted using Steen Happiness Index (SHI). The Hypothesis that proposed of the research is that there is a difference of happiness between the experimental group which was given mindfulness training treatment and controlled group which was not given the treatment of mindfulness training. The research design used was pre-test post-test control group design.The data obtained were analyzed using non- parametric Mann-Whitney to compare the differences of quality of life scores in pretest, posttest, and follow up between experimental groupand Control group. The result of this study showed that there are not a differences of happiness after the training between experimental group and control group after given, with value of Z = - 0.959, p = 0.337 (p > 0.05). in the post test and follow up, the group didn t show any differences of happiness with value of Z= -1.200, p = 0,230 (p>0.05).